The Effect of Corporate Governance Mechanisms on the Financial Performance of Banking Companies - Asep Effendi (Enrichment : Journal of Management, 2021)
The emergence of the Corporate Governance mechanism in the business world for the first time was caused by agency problems between capital owners and managers, where owners have difficulty ensuring that the funds invested are not taken over or invested in unprofitable projects so that they do not generate returns. Corporate governance is needed to unravel agency problems between fund owners and managers, besides that the implementation of Corporate Governance in every company organization turns out to have an impact on the management of financial performance and is able to affect a series of relationships between company management, the board of directors, shareholders and other stakeholders. This study uses a descriptive study method with a qualitative approach and data triangulation analysis, the results of the study explain that the importance of emphasizing the Corporate Governance system in the banking business is emphasized on several aspects, including those contained in the Indonesian Banking Good Corporate Governance guidelines issued by the Indonesian Banking Committee. The National Corporate Governance Policy in January 2004 stated that Good Corporate Governance (GCG) contains five main principles, namely openness, accountability, responsibility, independence and fairness and was created to protect the interests of all interested parties.